Summary and looking ahead - Chen, Kevin Z.; Hsu, Claire (International Food Policy Research Institute, 2016)
This book focuses on how China’s disaster management system— which is dedicated to the prevention, relief, and reconstruction efforts, carried out by the entire society, associated with the occurrence of natural hazards— performed during the Wenchuan earthquake. After briefly describing in Chapter 1 the earthquake’s effects, the government’s response, the evolution of China’s disaster management system, and the increasing attention paid by China’s government to disaster management in recent years, the remainder of the book focuses on key policy innovations throughout the disaster management process and system. It also covers the problems encountered, such as inadequate preparedness, misuse of funds, preference for short-term infrastructure projects over other projects that could better alleviate poverty, and inefficient allocation of funds. Below we summarize the key findings of the analysis of the relief and reconstruction efforts.